How to handle the job-offshoring backlash? - Terutomo Ozawa (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
Recent political development in the advanced economies, particularly in the US, signals a fast-growing backlash to MNEs' job-offshoring as a response to high wages at home. How best to tackle the issue must be rethought.
Keywords: 330